2007
DOI: 10.15174/au.2007.171
|View full text |Cite
|
Sign up to set email alerts
|

Distribución Geográfica del Alacranismo en el Estado de Guanajuato

Abstract: Introducción: El registro de picados por alacrán en el Estado de Guanajuato durante el periodo 2000 – 2005 rebasó en promedio los 24 000 casos por año, con una mortalidad promedio de 3 personas; afectando a núcleos de población, tanto del medio rural como urbano. A muchos años de haberse detectado la problemática, todavía se desconocen con precisión los aspectos epidemiológicos básicos de este fenómeno en el Estado. Material y Métodos: Se realizó un estudio retrospectivo, observacional y descriptivo de los año… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Regarding the seasonality, authors reported that in the State of Guanajuato scorpions have a predilection for warm and dry climate (Castillo‐Pérez et al ., ). This is confirmed in this study because during spring, the season with warm and dry climatic characteristics, the highest number of cases is reported in Morelos.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the seasonality, authors reported that in the State of Guanajuato scorpions have a predilection for warm and dry climate (Castillo‐Pérez et al ., ). This is confirmed in this study because during spring, the season with warm and dry climatic characteristics, the highest number of cases is reported in Morelos.…”
Section: Discussionmentioning
confidence: 97%
“…In the same way, Castillo and collaborators [8] performed an analysis of scorpionism in Mexico. Leynaud and Reati [9] conducted a foreign study on ophidism in Córdoba (Argentina) by using the SIGEpi program. And Pandey [10], who focused on ophidic risk in Nepal.…”
Section: Of 14mentioning
confidence: 99%